Physical and psychological aspects of anorexia nervosa based on duration of illness: a cross-sectional study - Takakura, Shu (Biopsychosoc Med, 2019)
BACKGROUND: We evaluated physical and psychological features of patients with anorexia nervosa (AN) who differed by duration of illness. METHODS: Data were obtained from 204 female patients with AN, divided into two groups based on illness duration: short-term illness duration (less than 5 years; n = 118); and long-term duration (5 years or more; n = 86). Physical parameters were measured using blood serum testing and psychological aspects were assessed using various instruments. RESULTS: A significantly higher proportion of restricting type AN was observed in the short-term group while the proportion of binge eating/purging type AN was higher in the long-term group. There was no difference in body mass index (BMI) between the groups. Serum total protein, albumin, potassium, chloride, and calcium in the long-term group were significantly lower than in the short-term group. Overall scores on the Eating Disorder Inventory as well as most of the subscales, except maturity fears, were higher in the long-term group than in the short-term group. The care subscale of the Parental Bonding Instrument (PBI) was lower in the long-term group than in the short-term group, while the overprotection subscale of the PBI was higher in the long-term group than in the short-term group. Results of a multiple regression analysis indicated that the overprotection subscale of the PBI was the only significant predictor of duration of illness. CONCLUSIONS: Duration of illness may be associated with physical and psychological features of AN; thus, adapting therapeutic approaches to illness duration might be necessary.